High genetic structure and low mitochondrial diversity in bottlenose dolphins of the Archipelago of Bocas del Toro, Panama: A population at risk? - Dalia C Barragán-Barrera; Laura J May-Collado; Gabriela Tezanos-Pinto; Valentina Islas-Villanueva; Camilo A Correa-Cárdenas; Susana Caballero (PLoS ONE, 2017)
The current conservation status of the bottlenose dolphin (Tursiops truncatus) under the IUCN is 'least concern'. However, in the Caribbean, small and localized populations of the 'inshore form' may be at higher risk of extinction than the 'worldwide distributed form' due to a combination of factors including small population size, high site fidelity, genetic isolation, and range overlap with human activities. Here, we study the population genetic structure of bottlenose dolphins from the Archipelago of Bocas del Toro in Panama. This is a small population characterized by high site fidelity and is currently heavily-impacted by the local dolphin-watching industry. We collected skin tissue samples from 25 dolphins to study the genetic diversity and structure of this population. We amplified a portion of the mitochondrial Control Region (mtDNA-CR) and nine microsatellite loci. The mtDNA-CR analyses revealed that dolphins in Bocas del Toro belong to the 'inshore form', grouped with the Bahamas-Colombia-Cuba-Mexico population unit. They also possess a unique haplotype new for the Caribbean. The microsatellite data indicated that the Bocas del Toro dolphin population is highly structured, likely due to restricted movement patterns. Previous abundance estimates obtained with mark-recapture methods reported a small population of 80 dolphins (95% CI = 72-87), which is similar to the contemporary effective population size estimated in this study (Ne = 73 individuals; CI = 18.0 - ∞; 0.05). The combination of small population size, high degree of genetic isolation, and intense daily interactions with dolphin-watching boats puts the Bocas del Toro dolphin to at high risk of extinction. Despite national guidelines to regulate the dolphin-watching industry in Bocas del Toro and ongoing educational programs for tour operators, only in 2012 seven animals have died due to boat collisions. Our results suggest that the conservation status of bottlenose dolphins in Bocas del Toro should be elevated to 'endangered' at the national level, as a precautionary measure while population and viability estimates are conducted.